2020
DOI: 10.1101/2020.04.30.069773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Personality, Subjective Well-Being, and the Serotonin 1a Receptor Gene in Common Marmosets (Callithrix jacchus)

Abstract: 1Of the three rating-based studies of common marmoset (Callithrix jacchus) personality, one 2 did not find domains resembling those labeled Conscientiousness or Openness. Because this 3 discrepancy may have been partly attributable to the fact that many purported markers of 4 Conscientiousness were excluded because of concerns about interrater reliability. We 5 therefore followed up this study by increasing the number of common marmosets that were 6 rated, bringing it up to 128 from 77. We also gathered the sa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 100 publications
(294 reference statements)
0
6
0
Order By: Relevance
“…Vasopressin and oxytocin are neuropeptides implicated in the development and maintenance of social behaviors in mammals ( Donaldson and Young, 2008 ; Meyer-Lindenberg et al, 2011 ). Recently, we showed that marmosets’ prosocial behaviors and individual variability are associated with the vasopressin V1a receptor gene ( AVPR1A ) and other genetic polymorphisms related to oxytocin and dopamine transmission ( Inoue-Murayama et al, 2018 ; Weiss et al, 2020 ). Based on these preliminary data, the NHP_NNP project plans to investigate the association of the neuroimaging-based brain connectome with genetic polymorphism and social behaviors.…”
Section: Bridging Neuroimaging Neuroanatomy and Beyondmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasopressin and oxytocin are neuropeptides implicated in the development and maintenance of social behaviors in mammals ( Donaldson and Young, 2008 ; Meyer-Lindenberg et al, 2011 ). Recently, we showed that marmosets’ prosocial behaviors and individual variability are associated with the vasopressin V1a receptor gene ( AVPR1A ) and other genetic polymorphisms related to oxytocin and dopamine transmission ( Inoue-Murayama et al, 2018 ; Weiss et al, 2020 ). Based on these preliminary data, the NHP_NNP project plans to investigate the association of the neuroimaging-based brain connectome with genetic polymorphism and social behaviors.…”
Section: Bridging Neuroimaging Neuroanatomy and Beyondmentioning
confidence: 99%
“…For the social behaviors of marmosets, we plan to perform reliable assessments by a well-established personality rating scale, Hominoid Personality Questionnaire ( Weiss, 2017 ; Weiss et al, 2009 ), which proved to be reproducibly correlated with other biological markers and genotyping in marmosets ( Inoue-Murayama et al, 2018 ; Weiss et al,2020 ) . The reliability of this behavioral analysis is based on long-term housing and observations (>one year) by the animal keepers.…”
Section: Bridging Neuroimaging Neuroanatomy and Beyondmentioning
confidence: 99%
“…Common marmosets ( Callithrix jacchus ) are highly social cooperatively breeding New World primates that live in cohesive family groups in a variety of different habitats, from the Atlantic rain forest to the semiarid area of shrub forests (Garber et al, 2019) and have been studied in a variety of socio‐cognitive questions (Schiel & Souto, 2017). In recent years, these monkeys have become the focus of personality studies under lab conditions: they display consistent interindividual differences when assessed in a battery of experiments (Díaz et al, 2020; Koski & Burkart, 2015; Šlipogor et al, 2016; Tomassetti et al, 2019), observations (Martin et al, 2019; Masilkova et al, 2020; Šlipogor et al, 2020), questionnaires (Inoue‐Murayama et al, 2018; Koski et al, 2017; Weiss et al, 2020), and by using a combination of several different personality assessment methods (Iwanicki & Lehmann, 2015; Šlipogor et al, 2020). However, little is known about long‐term consistency of their personality structure, and no study to this date assessed the personality of wild common marmoset populations.…”
Section: Introductionmentioning
confidence: 99%
“…1A third study of common marmosets by Inoue-Murayama et al (2018) did not find a Conscientiousness domain although that does not appear to be the last word for that sample (Weiss et al, 2020). …”
mentioning
confidence: 94%
“…Dolphins, for example, form complex social bonds (Lusseau et al, 2006;Moreno & Acevedo-Gutiérrez, 2016), use tools and display cultural traditions (Krützen et al, 2005), engage in prosocial behavior (Nakahara et al, 2017), possess cognitive abilities related to imitation, cooperation, and vocal recognition (Bruck, 2013;Jaakkola et al, 2010Jaakkola et al, , 2018, have nonconceptive sex (Furuichi et al, 2013), and engage in sexual coercion and Machiavellian behavior (Kuczaj et al, 2001;Wallen et al, 2016). Thus, overlapping dolphin and primate personality structures would suggest that characteristics of primates that are not shared with dolphins (e.g., 1 A third study of common marmosets by Inoue-Murayama et al (2018) did not find a Conscientiousness domain although that does not appear to be the last word for that sample (Weiss et al, 2020).…”
mentioning
confidence: 99%